Tipologi Kesalahan Penentuan Wazan Fi'il dan Faktor Penyebabnya dalam Pembelajaran Ilmu Sharaf - Khanifatun Nisa’; Kafin Jaladri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to describe the types of errors made by eighth-grade students at Pondok Pesantren Miftahul Huda KMA Al Wustho in determining verb patterns (wazan fi‘l), identify the factors contributing to these errors, and describe the teachers’ efforts to overcome them. This research employed a descriptive qualitative approach with a case study design. Data were collected through interviews with teachers and students, classroom observations, and documentation. The research subjects were 32 eighth-grade students who had studied ṣarf using the Al-Amtsilah Al-Tashrifiyah textbook. The findings indicate that, among the 32 students who completed the 14 test items, a total of 120 errors were identified, consisting of 109 letter-related errors (90.8%) and 11 vowel-marking errors (9.2%). The most frequent type of letter error was addition (62.4%), followed by inversion (15.6%), substitution (12.8%), and omission (9.2%). The highest error rates in determining verb patterns occurred in the if‘aw‘ala pattern (اِفْعَوْعَلَ), with an error rate of 84.4%, followed by the ifta‘alla pattern (اِفْتَعَلَّ), with an error rate of 40.6%. The factors contributing to these errors included the complexity of wazan structures and the rules of i‘lāl, insufficient independent practice and lack of specific exercises distinguishing one wazan from another, as well as students’ low motivation and lack of accuracy. To address these difficulties, teachers have employed several instructional strategies, including lectures, explanations using the whiteboard, group discussions, dictionary use, language games, and regular review of previously taught materials. However, these methods have not yet been fully effective due to the lack of structured exercises specifically designed to address complex wazan patterns